Marine-Sediment Characteristics and Thickness Over The Eroded Sayung Coast, Demak, Indonesia - Wisnu Arya Gemilang; Ulung Jantama Wisha; Guntur Adhi Rahmawan; Koko Ondara (Politeknik Kelautan dan Perikanan Dumai, 2021)
An over whelming erosion occurred in Sayung waters is related to sedimentary processes. That is why the deeper determination of sediment characteristics through direct survey and acoustic data retrieval is crucial. Several previous related studies had been conducted revealing the rate and model of sedimentation. This study aimed to describe the sedimentary processes according to its features and deposition. In this study, we conducted a grab-sampling, bathymetry surveys and also hydrodynamical model. Grain size analysis was employed to observe the characteristics of sediment and its deposition environment. At the same time, we applied dual-frequency bathymetry data for estimating sediment thickness which reflects the accumulation sediment over Sayung waters. We found that sediment texture varies from sand to clay, while coarse sediment fraction is dominant in the western part. Near the coastline area of Sayung waters reflecting the more potent transport mechanism in the deposition environment, proven by the less-accumulated sediment from 0-2.5 km from the coastline. In sea-ward regions, we observed the finer sediment fraction, showing that the low-transport mechanism takes place. The topographical alteration has intensively occurred at 2.5-3.2 km from the coastline. Tidal current has an essential role in inducing local transport whereby the speed varies ranging from 0-0.14 m/s, other than that, the more substantial current features have observed in Surodadi and Bedono coast moving perpendicularly toward the beach. In contrast, in the southern Sayung waters, the current profiles tend to be weak inducing higher sedimentation. Besides, the emergence of the sandbar has a role in reflecting sediment texture predomination in Sayung waters.